2005
DOI: 10.1177/1049731505276412
|View full text |Cite
|
Sign up to set email alerts
|

Empowering High-Risk Families of Children With Disabilities

Abstract: Objective: This study evaluated an adapted version of a group-based manualized parent education curriculum applied to meet the parenting needs of high-risk African American families rearing children with developmental delays. Methodology: Three successive cohorts were assessed for statistical equivalence and evaluated using a one group pre-and postdesign followed by a booster session. Dependent variables used self-reports of caregivers' empowerment, emotional outlook, parent-child interaction, and community in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Empowerment related to parenthood has been defined as a process by which families can access knowledge, skills and resources that enable them to gain positive control over their own lives (Singh et al 1995). Parental empowerment is associated with lower levels of stress (Nachshen & Minnes 2005) and depressive symptoms (Martinez et al 2009), as well as improved family functioning (Cunningham et al 1999) and ability to solve problems (Farber & Maharaj 2005). Parental empowerment is associated with lower levels of stress (Nachshen & Minnes 2005) and depressive symptoms (Martinez et al 2009), as well as improved family functioning (Cunningham et al 1999) and ability to solve problems (Farber & Maharaj 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Empowerment related to parenthood has been defined as a process by which families can access knowledge, skills and resources that enable them to gain positive control over their own lives (Singh et al 1995). Parental empowerment is associated with lower levels of stress (Nachshen & Minnes 2005) and depressive symptoms (Martinez et al 2009), as well as improved family functioning (Cunningham et al 1999) and ability to solve problems (Farber & Maharaj 2005). Parental empowerment is associated with lower levels of stress (Nachshen & Minnes 2005) and depressive symptoms (Martinez et al 2009), as well as improved family functioning (Cunningham et al 1999) and ability to solve problems (Farber & Maharaj 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 18 studies that reported sample demographics, 10 had a sample that was predominantly (≥74%) White or of European origin. Four studies (Chernoff et al, ; Ireys et al, ; Kutash et al, ; Silver et al, ) included a racially and ethnically diverse sample and four (Farber & Maharaj, ; Magaña et al, ; Pilon & Smith, ; Thomas et al, ) specifically targeted racial/ethnic minorities. In most studies, the intervention was administered in English ( n = 17) or in another language dominant in the study region (Dellve et al, ; Picard et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies evaluated psychoeducational group‐based interventions. Four were based on theories of family stress and coping (Farber & Maharaj, ; Jerram et al, ; Picard et al, ; Schultz et al, ); one was based on patient activation literature (Thomas et al, ). Interventions sought to improve parental management by addressing family relationships (Jerram et al, ; Picard et al, ), coping (Jerram et al, ; Schultz et al, ), problem‐solving (Farber & Maharaj, ; Schultz et al, ), advocacy, and ability to access services (Farber & Maharaj, ; Jerram et al, ; Picard et al, ; Schultz et al, ; Thomas et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myers, Vander, and Lobdell (2013) successfully utilized the FES to demonstrate the feasibility of a telemental health/videoconferencing to provide care usually delivered in person, targeting families raising children with attention deficit disorder. Farber and Maharaj (2005) found the FES to be sensitive to the effects of a parent education program designed for African American families raising developmentally delayed children. In parallel fashion, Weiss, Viecili, Sloman, and Lunksy (2013) found the FES to reflect the gains for parents whose children with autism participated in social skills training, and Resendez, Quist, and Matshazi (2000) found FES knowledge scores to increase among parents over time who had participated in the Vanderbilt Family Empowerment Project.…”
Section: Introductionmentioning
confidence: 99%